If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + 7) = 5(4 + -1x) Reorder the terms: 5(7 + 2x) = 5(4 + -1x) (7 * 5 + 2x * 5) = 5(4 + -1x) (35 + 10x) = 5(4 + -1x) 35 + 10x = (4 * 5 + -1x * 5) 35 + 10x = (20 + -5x) Solving 35 + 10x = 20 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 35 + 10x + 5x = 20 + -5x + 5x Combine like terms: 10x + 5x = 15x 35 + 15x = 20 + -5x + 5x Combine like terms: -5x + 5x = 0 35 + 15x = 20 + 0 35 + 15x = 20 Add '-35' to each side of the equation. 35 + -35 + 15x = 20 + -35 Combine like terms: 35 + -35 = 0 0 + 15x = 20 + -35 15x = 20 + -35 Combine like terms: 20 + -35 = -15 15x = -15 Divide each side by '15'. x = -1 Simplifying x = -1
| 7(3x+4)=10-3x | | 25x(x+3)=8500 | | 15x^2-14x-57=0 | | x+1y=2x-1 | | g(1)=2(1)+4 | | 6a+6=4a-1 | | 3x-2+4x+x+12=66 | | 12x^2+18=30 | | mp+mq=r | | 3(x-4)=2(x-3) | | 21x-6+5=26 | | 5v-9=3v+1 | | 3(5-5)= | | 88=7x+5x+4 | | -12x+7=4x-9 | | 7v-9=4v+3 | | 81t^2-144t+64= | | 5(2+t)-2(t+1)= | | 6v-4=5v+4 | | 16s^2-56s+49= | | b=75+(15+6)w | | (-2xy^2)(3x^2y^4)= | | x(x+7)=120 | | v-5/3-v=-3(v-1) | | 8n-(6n+5)=7 | | 190-2x+x+10=180 | | 2x-1=y | | 2x+10=y | | 4+4x/3=6 | | 2x-13=y | | -3x+5=y | | 3x+6=33 |